Environmental phenol mixture during pregnancy and child sleep quality in the ECHO cohort - Geiger, Sarah D.; Xun, Xiaoshuang; Zhang, Cai; Chandran, Aruna; Madan, Kritika; Kim, Grace; Naveed, Fatima; Woodbury, Megan; Goin, Dana E.; Eick, Stephanie M.; Blackwell, Courtney K.; Mansolf, Maxwell; et al. (Frontiers in Pediatrics, 2025)
IntroductionPoor sleep quality in childhood can predict sleep quality throughout the lifecourse and other health outcomes. Endocrine-disrupting chemicals can affect adults’ sleep quality, and prenatal phenol exposure impacts fetal development.ObjectiveTo assess associations between prenatal phenol concentrations and child sleep outcomes.MethodsWe used data from the National Institutes of Health-funded Environmental influences on Child Health Outcomes (ECHO) Cohort (n = 1,198) that were collected from 2008 to 2019 at several sites across the United States. The present analysis was conducted in 2023–2024. Using single-pollutant and mixture models, we examined associations between prenatal phenol concentrations and three key child sleep quality outcomes: sleep problems, disturbance, and impairment. Child sleep outcomes were assessed using the Child Behavior Checklist (CBCL) and the Patient-Reported Outcomes Measurement Information System (PROMIS) Sleep Disturbance and Sleep-Related Impairment scales. Unadjusted and multivariable-adjusted models were examined, with stratified models and interaction terms used to examine interactions with child sex.ResultsOf the eight phenols assessed, higher prenatal methylparaben concentrations were associated with lower child sleep-related impairment scores (β = −4.79, 95% CI: −9.45 to −0.14). Sex modified the associations for benzophenone-3 and PROMIS sleep disturbance T-scores, where the association was stronger among boys (tertile 3 vs. 1, β = 3.20; 95% CI: 0.27–6.14; p = 0.033) and did not persist among girls. Bisphenol A was associated with sleep-related impairment among boys (tertile 2 vs. 1, β = −5.69; 95% CI: 0.55–10.82; p = 0.031). Phenol mixtures were not associated with sleep outcomes overall or by sex.ConclusionThe findings suggest that phenol exposure during pregnancy may be associated with child sleep quality and that child sex modifies this association.